Peritoneal Carcinomatosis in Gastro-Entero-Pancreatic Neuroendocrine Neoplasms: Clinical Impact and Effectiveness of the Available Therapeutic Options - Merola, Elettra; Prasad, Vikas; Pascher, Andreas; Pape, Ulrich Frank; Arsenic, Ruza; Denecke, Timm; Fehrenbach, Uli; Wiedenmann, Bertram; Pavel, Marianne Ellen (Neuroendocrinology, 2020)
BACKGROUND: Peritoneal carcinomatosis (PC) can affect the quality of life of patients with gastro-entero-pancreatic neuroendocrine neoplasms (GEP-NENs). Peritoneal disease control by medical therapies in these patients has been poorly investigated Objectives: To describe, in a consecutive series of GEP-NENs, the clinical impact of PC and to report the effectiveness of available treatments in PC control. METHODS: A retrospective, monocenter analysis was performed of 135 GEP-NENs (1993-2016) with at least a 12-month follow-up. Peritoneal disease progression was defined as detection of a significant increase in size or appearance of new implants by imaging. RESULTS: A total of 62.9% of cases had diffuse PC (involving at least 2 abdominal quadrants). According to WHO 2017 classification, cases were 42.3% neuroendocrine tumors NET-G1, 45.5% NET-G2, 6.5% NET-G3, 4.9% neuroendocrine carcinomas NEC-G3, and 0.8% mixed neuroendocrine-nonneuroendocrine neoplasms. Bowel obstruction occurred in 30 (22.2%) patients mainly depending on size of peritoneal implants (HR: 1.10; 95% CI: 1.02-1.20; p = 0.01). Patients with diffuse PC treated with peptide receptor radionuclide therapy (PRRT) showed peritoneal progression in 37.5% of cases, and bowel obstruction or ascites in 28.1%. Better peritoneal disease control was observed in cases receiving somatostatin analogs at first-line therapy, probably due to a less aggressive disease behavior for these patients. CONCLUSIONS: Bowel obstruction is not uncommon in GEP-NENs with PC. PRRT should be adopted with caution in GEP-NENs with diffuse PC, but larger series are needed to confirm these data.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Bowel obstruction; Disease control; Neuroendocrine neoplasms; Peptide receptor radionuclide therapy; Peritoneal carcinomatosis